Ballistic-like space-charge-limited currents in halide perovskites at room temperature - Almora, Osbel; Miravet, Daniel; Garcia-Batlle, Marise; Garcia-Belmonte, Germa (Applied Physics Letters, 2021)
The emergence of halide perovskites in photovoltaics has diversified the research on this material family and extended their application toward several fields in the optoelectronics, such as photo- and ionizing-radiation-detectors. One of the most basic characterization protocols consists of measuring the dark current-voltage ( J - V) curve of symmetrically contacted samples for identifying the different regimes of the space-charge-limited current (SCLC). Customarily, J & PROP; V-n indicates the Mott-Gurney law when n & AP; 2 or the Child-Langmuir ballistic regime of SCLC when n = 3 / 2. The latter has been found in perovskite samples. Herein, we start by discussing the interpretation of J & PROP; V-3/2 in relation to the masking effect of the dual electronic-ionic conductivity in halide perovskites. However, we do not discard the actual occurrence of SCLC transport with ballistic-like trends. Therefore, we introduce the models of quasi-ballistic velocity-dependent dissipation (QvD) and the ballistic-like voltage-dependent mobility (BVM) regimes of SCLC. The QvD model is shown to better describe electronic kinetics, whereas the BVM model results are suitable for describing both electronic and ionic kinetics in halide perovskites as a particular case of the Poole-Frenkel ionized-trap-assisted transport. The proposed formulations can be used as the characterization of effective mobilities, charge carrier concentrations and times-of-flight from J - V curves, and resistance from impedance spectroscopy spectra.& nbsp;(C) 2021 Author(s). All article content, except where otherwise noted, is licensed under a Creative Commons Attribution (CC BY) license (http://creativecommons.org/licenses/by/4.0/).
CRIS-Team WoS Importer:2021-12-31